Fetal Alcohol Syndrome: Impact on Neurodevelopment, Diagnosis, Early Intervention and Motor Disorders in Children under 3 Years - Adamczyk, Sabina; Przygoda, Maria; Włodyka, Jagienka; Stępień, Kamila; Trestka, Gabriela; Zelik, Urszula; Dziewic, Jakub; Śnieżna, Joanna; Florczak, Wojciech; Domino, Wiktoria; Dzwonnik, Karol (Quality in Sport, 2025)
Fetal Alcohol Syndrome (FAS) is the most severe outcome of prenatal alcohol exposure, characterized by a combination of somatic and neurological abnormalities, including facial dysmorphism, growth deficits, and neurocognitive impairments. Fetal Alcohol Spectrum Disorders (FASD) encompass a broader range of outcomes from prenatal alcohol exposure, with varying degrees of severity. Alcohol consumption during pregnancy can disrupt fetal development, with no known safe threshold for its intake at any stage of gestation. The consequences are particularly profound on the central nervous system (CNS), where damage to structures like the cerebellum can lead to motor dysfunctions, balance issues, and cognitive impairments. Early identification and diagnosis of FAS or FASD, especially during the critical first years of life, is essential for improving developmental outcomes. Intervention strategies, including physical and cognitive therapy, can help mitigate long-term disabilities associated with these conditions. Diagnostic methods, such as ultrasound for fetal structural abnormalities and the AUDIT screening tool, are integral for early detection. This review highlights the impact of prenatal alcohol exposure on motor skill development, particularly the persistence of primitive reflexes in infants with FAS, which is indicative of CNS immaturity and necessitates early therapeutic interventions. Understanding these motor and neurological markers is critical for providing appropriate support and improving outcomes for affected children.